Blind versus wise use of CAS - Kovács, Zoltán (Teaching Mathematics and Computer Science, 2007)
During my courses for mathematics major students I often use technology linked to the arising problems. In such cases I noted that some students were used to learn just some procedures, which made them able to solve (partially) some problems and when they got the result, they accepted it passively and did not relate it to the initial problem.In this paper I outline a strategy and investigate some simple exercises about how to develop a critical attitude towards the results obtained by technology in an introductory course to CAS.I believe that wise use of technology offers an effective method in teaching mathematics, without reducing the students' mental contribution.